2009
DOI: 10.1681/asn.2008020130
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Phosphate-Binding Chewing Gum Reduces Hyperphosphatemia in Dialysis Patients

Abstract: In uremic patients, hyperphosphatemia is associated with cardiovascular calcification and increased cardiovascular mortality. Despite the use of phosphate binders, only half of hemodialysis (HD) patients achieve recommended serum phosphate levels. A hyperphosphoric salivary content, which correlates linearly with serum phosphate, has been reported in HD patients. We hypothesized that binding salivary phosphate during periods of fasting in addition to using phosphate binders with meals could improve the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 23 publications
(49 reference statements)
2
60
3
1
Order By: Relevance
“…These results were in (9) who found that serum phosphate significantly decreased during the first weeks of chewing chitosan gum in ESRD patients and returned to baseline after discontinuing the chewing gum. Our results were not in agreement with Akizawa T et al,2014 (10) who found that chewing gum and expelling saliva does not affect serum and salivary phosphorus levels in Japanese HD patients with hyperphosphatemia.…”
Section: Discussionmentioning
confidence: 85%
“…These results were in (9) who found that serum phosphate significantly decreased during the first weeks of chewing chitosan gum in ESRD patients and returned to baseline after discontinuing the chewing gum. Our results were not in agreement with Akizawa T et al,2014 (10) who found that chewing gum and expelling saliva does not affect serum and salivary phosphorus levels in Japanese HD patients with hyperphosphatemia.…”
Section: Discussionmentioning
confidence: 85%
“…Blood samples from 13 previously studied chronic HD patients, 8 9 males and 4 females, age range 30-71 years, dialytic age range 12-264 months, were used for the determination of hsCRP and its relationship with hyperphosphatemia and Ca × PO 4 . The etiology of ESRD for the patients was as follows: chronic glomerulonephritis (four patients); nephroangiosclerosis (seven patients); polycystic kidney disease (one patient); undiagnosed (one patient).…”
Section: Methodsmentioning
confidence: 99%
“…The etiology of ESRD for the patients was as follows: chronic glomerulonephritis (four patients); nephroangiosclerosis (seven patients); polycystic kidney disease (one patient); undiagnosed (one patient). As in the Methods section of our previously published papers and in accordance with the previously reported protocols, [6][7][8] exclusion criteria for the enrollment of the patients comprised the diagnosis of acute infections, malignancies, ongoing inflammatory processes, and Sjögren syndrome, which directly may influence CRP level.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations